PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA PERAWAT DI RUANG RAWAT INAP RSUD UNDATA PALU - Sipatu, Lindanur (Katalogis, 2013)
This research aims to know and analyze simultaneous and partial effects of motivation, work environment and job stress on nurse’s performance at overnight care room in Regional Public Hospital Undata Palu. This is a descriptive and causal research using proportionate random sampling as the sampling technique to collect data from 125 nurses. This research employs multiple linear regression as an analysis tool. Based on the results of descriptive statistics, it show that mean of motivation variable is sense of belonging 3.94. The highest mean work environment variable is psychological work environment 3.60. Furthermore, the highest mean of job stress variable is group support 4.17 and for nurse’s performance is capability 4.18 respectively. Based on the result of multiple linear regression, it show that F value = 34.490 at the significant level of 0.000 (α = 0,05). This indicates of motivation, work environment and job stress simultaneously perform positive and significant effects of nurse’s performance at overnight care room in Regional Public Hospital Undata Palu. Meanwhile, partially motivation and work environment perform positive but not sognificant effects on performance. In addition, job stress perform positive and significant effect on nurse’s performance overnight care room in Regional Public Hospital Undata Palu.